The Effect of Expected Benefit and Perceived Cost on Employees’ Knowledge Sharing Behavior: a Study of It Employees in India - Gupta, Bindu; Joshi, Sahil; Agarwal, Mohit (Organizations and Markets in Emerging Economies, 2012)
In the increasingly turbulent business environment knowledge is considered to be the most important source of sustainable competitive advantage and to sustain it, an organization must create, share, and utilize the knowledge it possesses. The critical knowledge is only available to the organization as long as employees are willing to cooperate. It can easily be lost if the employees decide to explore other opportunities outside the organization or employees fear to share knowledge with co-workers. To achieve continuous growth, organizations need to understand the factors which motivate and de-motivate the employees to share knowledge. The present study examines the impact of employees’ perception of perceived benefits and cost of knowledge sharing on their knowledge sharing behavior. Data were collected from 228 employees of two major Information Technology organizations in India. The results of regression analysis showed that benefits mainly perceived increase in expected association with others and expected contribution to organization positively influences employees’ knowledge sharing behaviour. Perceived cost was found to influence negatively on knowledge sharing behaviour. The findings of the study are expected to provide significant inputs to organizations to design the practices which make knowledge sharing an integral part of the day-to-day conversation.